Young-Onset Amyotrophic Lateral Sclerosis: Genetic Structure and Phenotypic Features - Denis V. Shevchuk; Natalya Yu. Abramycheva; Arina R. Protsenko; Darya A. Grishinа; Angelina G. Makarova; Maria N. Zakharova (Анналы клинической и экспериментальной неврологии)
Introduction. Young-onset amyotrophic lateral sclerosis (yALS) is a rare neurodegenerative disease characterized by the onset of clinical manifestations before the age of 45. The global prevalence, incidence, and genetic structure of yALS remain largely unknown, and the diagnosis is based primarily on clinical presentation, neurophysiologic findings, and molecular genetic analysis.